Model of the optimal allocation of heterogeneous resources in a vertically integrated company - Sysoiev, Volodymyr Viktorovych (University of Miskolc, 2017)
One of the main problems of management in a vertically integrated company – the allocation of heterogeneous resources between its organizational units in conditions a limited budget is considered. Mathematical models of the optimal allocation of heterogeneous resources are proposed, taking into account the importance of different types of resources and priorities of organizational units of the company that take into account the types of tasks they perform and the types of activity.